EFEKTIVITAS IKLAN DALAM MERAIH PARTISIPASI POLITIK - Retnowati, Yuni (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2013)
In Indonesia a great political advertising budget has been spent on some media. Television as a medium thatabsorbed the largest share of advertising play important roles in the spread of political advertising. Most of thecontent of the advertising message is directed to candidates imaging by displaying false impressions and circumstancesthat does not actually. One of the goals of political advertising is currently to persuade audience toparticipate in election and vote for candidates from a political party who advertise. The effectiveness of advertisingpolitical questionable because frequently found groups who does not participate in the election. As part ofthe marketing communication, advertising cant work alone to gain public support and participation. Integratedmarketing communication is the right solution to help improve political participation other than to be followed bythe candidates credibility and clarity offered programs of political parties.